MEDIA PEMBELAJARAN BERBASIS VIDEO TUTORIAL TEKNIK DASAR BOLA VOLI PADA PELAJAR SMA KELAS X - Sabaruddin Yunis Bangun; Nurul Nisa Nasution; R. Syaifullah D. Sihombing (Riyadhoh : Jurnal Pendidikan Olahraga, 2023)
The purpose of this study was to develop video tutorial-based learning media for basic volleyball techniques for Class X high school students. The research method used in this study was a Research and Development (R&D) development research method with a quantitative approach. The population in this study were high school students of Class X SMA and the samples in this study were 30 students divided; 10 students tested the feasibility of video tutorials on basic volleyball techniques and 20 students tested the use of video tutorials on basic volleyball techniques. Data collection techniques in this study used questionnaires/questions given to experts and students. The data analysis technique used in this study is using percentages. The results of the product trials for the feasibility of video tutorials for basic volleyball techniques were 82% and trials for using video tutorials for basic volleyball techniques were 87%. The conclusion of this study is that video tutorials on basic volleyball technique tutorials for Class X high school students can improve student learning outcomes when passing volleyball.